Los realismos en Beatus Ille de Antonio Muñoz Molina. - Papa Mamour Diop (Ogigia, 2007)
ENGLISH: This work deals with the current debate about reality and its literary and artistic expression: realism. In Beatus Ille, Antonio Muñoz Molina’s first novel, the fictional universe reveals three kinds of realism: the epic and elegiac realism, the historic realismand the magic realism. SPANISH: En este trabajo, abordamos el actual debate sobre la realidad y su expresión literaria y artística: el realismo. En Beatus Ille, primera novela de Antonio Muñoz Molina, eluniverso novelesco permite percibir tres tipos de realismos: el realismo épico elegiaco, el realismo histórico o contrafactual y el realismo mágico.